Aging and inequality: The perspective of labor income share - Chen Wang; Guanghua Wan; Zhi Luo; Xun Zhang (Asian Development Bank Institute (ADBI), 2017)
Despite a growing literature on population aging, empirical studies exploring mechanisms between aging and income inequality are scarce. This paper estimates the impact of aging on inequality via the perspective of labor income share, based on cross-country information covering the period 1990-2010. Two transmission mechanisms are examined - aging leads to a declining labor share and affects the average wage. Our robust finding shows that (i) there is a positive impact of aging on income inequality, (ii) this positive impact is because aging leads to a lower share of labor income, and (iii) more specifically, the labor share-reducing effect of aging comes from the shrinking labor force rather than the lowering of the average wage.
Keywords: E25; J11; J14; J21; 330; income inequality; aging; labor share; functional distribution of income